Do defects in PAHs promote catalytic activity in space? Stone–Wales pyrene as a test case. Issue 12 (13th March 2020) - Campisi, Dario; Candian, Alessandra
Abstract : Using density functional theory (DFT), we studied the formation of H2 on Stone–Wales pyrene. Abstract : Using density functional theory (DFT), we studied the formation of Stone–Wales defects in pyrene, as a prototype PAH molecule. In addition, we studied the reactivity of the defective and pristine pyrenes toward hydrogenation, a process that can occur in some regions of the interstellar medium. We found that the formation of the defect requires overcoming energies of the order of 8.4 eV, but the defective structure is stable due to the high reverse reaction barrier (approx. 6 eV). We also found that the presence of the defect decreases the sticking barrier for the first hydrogenation and promotes more stable singly and doubly hydrogenated intermediates with respect to that of the pristine pyrene. Finally, our results show that both Stone–Wales pyrene and pristine pyrenes can lead to the formation of H2 through an extraction mechanism involving H atoms attached on distal carbon atoms with energy barriers below 2 eV.